2019
DOI: 10.1371/journal.pone.0226155
|View full text |Cite
|
Sign up to set email alerts
|

Insights of organic fertilizer micro flora of bovine manure and their useful potentials in sustainable agriculture

Abstract: Exploration of diverse environmental samples for plant growth-promoting microbes to fulfill the increasing demand for sustainable agriculture resulted in increased use of bacterial biofertilizer. We aimed for the isolation of plant growth-promoting as well as antibiotic sensitive bacteria from bovine manure samples. The basic theme of our study is to highlight potentials of bacteria in manure and the unchecked risk associated with the application of manure i.e. introducing antibiotic-resistant microbial flora,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This uptake generally occurs during acidification of the soil rhizosphere through organic acid production. While studies have been found reporting Ca and Mg solubilization and S oxidation activity by bacteria [ 81 , 82 , 83 ], hardly any have been reported in yeasts. Falih and Wainwright (1995) reported the yeasts Williopsis californica and S. cerevisiae as capable of oxidizing elemental S in vitro to produce thiosulfate, tetrathionate and sulfate [ 84 ], but no yeasts with this ability have been reported recently.…”
Section: Yeasts As Biostimulant and Biofertilizer Agentsmentioning
confidence: 99%
“…This uptake generally occurs during acidification of the soil rhizosphere through organic acid production. While studies have been found reporting Ca and Mg solubilization and S oxidation activity by bacteria [ 81 , 82 , 83 ], hardly any have been reported in yeasts. Falih and Wainwright (1995) reported the yeasts Williopsis californica and S. cerevisiae as capable of oxidizing elemental S in vitro to produce thiosulfate, tetrathionate and sulfate [ 84 ], but no yeasts with this ability have been reported recently.…”
Section: Yeasts As Biostimulant and Biofertilizer Agentsmentioning
confidence: 99%
“…The height of the plants was significantly higher when BM was applied. It is probable that the microbial community in these samples can promote plant growth [37]. There were no significant differences between the fresh and dry weight of the plants grown in soil to which BM and BMRSM sludges were added.…”
Section: Evaluation Of the Solid Residue Obtainedmentioning
confidence: 93%
“…One gram of the fresh BSFL frass sample was suspended in 99 mL of sterile distilled water and shaken for 2 to 5 minutes [10]. The solution was thoroughly mixed and diluted with levels of 10 -1, 10 -2, 10 -3, 10 -4 and 10 -5 .…”
Section: Bsfl Faeces Bacteria Isolationmentioning
confidence: 99%